Consequences of family-supportive supervisor behaviour: A meta-analytic review - Yuxiang Luan; Guolong Zhao; Nan Wang (South African Journal of Business Management)
Purpose: Significant academic focus has been placed on family-supportive supervisor behaviour (FSSB), yet findings remain inconsistent, challenging field advancement. This study aims to conduct a comprehensive meta-analysis of FSSB and its outcomes.